ULTRASONIC TREATMENT IMPACT ON THE STABILITY OF AQUEOUS DISPERSIONS OF INORGANIC AND ORGANIC PIGMENTS IN THE PRESENCE OF SURFACTANTS - Aleksandrova, Yulia; Budanova, Natalia; Farmakovskaya, Ariadna; Okorokova, Nadezhda; Ustyuzhaninova, Galina; Zharova, Nelli; Kohlert, Victoria (Revista Inclusiones, 2020)
The colloidal stability of aqueous dispersions of the inorganic pigment Fe2O3 (red) and the organic pigment of copper phthalocyanine CuPc (blue), which were treated in an ultrasonic field in the presence of water-soluble polymers and surfactants, was studied. In the presence of ethyl hydroxyethyl cellulose (EHEC), ultrasonic treatment leads to a significant increase in the stability of aqueous Fe2O3 dispersions, while the sizes of the pigment particles decrease from 1 μm to 0.3 μm, and the particle size distribution becomes narrower. For aqueous dispersions of CuPc, mechanochemical modification of the surface removes the wettability problem and obtain intensely colored stable aqueous dispersions of this pigment.